Whistle Blowing System Sebagai Akselerasi Transformasi Birokrasi Berbasis Digital Di Pemerintah Kota Bandar Lampung - Izzati, Nabila Firstia; Perbawati, Candra (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The goal and aspiration of every country is to realize good, clean, and authoritative governance (clean and good governance). In addition to the government and the state, the concept of governance also includes the participation of other actors outside the entity, thus involving various parties. An example of a method to succeed good and clean governance is by implementing a Whistle Blowing System that arises due to the actions of the Whistle Blower which can be a system used to realize the acceleration of digital-based bureaucratic transformation in the Bandar Lampung City Government. This study uses a statutory approach (statue approach). The socio-legal approach is used to examine and study the issue of study by examining social phenomena related to the application of the whistle blowing system as an effort to realize digital-based bureaucratic transformation, as well as norms, related legal doctrines, and the application of both. The policy formation of the Bandar Lampung City Government, transformation, and digital-based bureaucracy are elaborated using a statutory approach. The urgency of this research is to examine and optimize the whistle blowing system in accelerating digital-based bureaucratic transformation in the Bandar Lampung City Government. Also the out put in this study is a scientific article to be published at scientific meetings and journals both international and national.